2019
DOI: 10.1109/led.2019.2931947
|View full text |Cite
|
Sign up to set email alerts
|

Stateful Logic Operations in One-Transistor-One- Resistor Resistive Random Access Memory Array

Abstract: Nonvolatile and cascadable stateful logic operations are experimentally demonstrated within a 1 k-bit one-transistor-one-resistor (1T1R) resistive random access memory (RRAM) array, where NAND gates serve as the building blocks. A robust dual-gate-voltage operation scheme is proposed. The effects of the transistor ON logic operation and the robustness to device parameter variations are discussed. The parallel 4-bit bitwise XOR operation is experimentally implemented in the 1T1R array by cascading NAND gates. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 25 publications
(17 reference statements)
0
30
0
Order By: Relevance
“…It must be noted that even the NOR logic primitive is implemented with modifications to the peripheral circuitry of the conventional memory array, namely the row decoder (modified to bias the rows at 'isolation voltage' to prevent unintended NOR operation in those rows) and the WRITE circuitry (modified to apply the MAGIC execution voltage which is twice the WRITE voltage). Similarly, in the NAND-based logic family reported in [37], XOR gate is implemented as a sequence of four NAND operations. This implies that if the fundamental logic primitive of a memristive logic family is weak, all in-memory computation performed using that logic family will be in-efficient (requiring long sequences of operations).…”
Section: Memristive Logicmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted that even the NOR logic primitive is implemented with modifications to the peripheral circuitry of the conventional memory array, namely the row decoder (modified to bias the rows at 'isolation voltage' to prevent unintended NOR operation in those rows) and the WRITE circuitry (modified to apply the MAGIC execution voltage which is twice the WRITE voltage). Similarly, in the NAND-based logic family reported in [37], XOR gate is implemented as a sequence of four NAND operations. This implies that if the fundamental logic primitive of a memristive logic family is weak, all in-memory computation performed using that logic family will be in-efficient (requiring long sequences of operations).…”
Section: Memristive Logicmentioning
confidence: 99%
“…As already stated, a memristive logic family cannot implement such a heterogeneity of gates. As illustrated in Figure 6, the XOR gate has to be implemented as NAND gates [37,49], increasing the logic levels to 12. Such an eight-bit PP adder (Sklansky) is expressed in OR/AND logic primitive and implemented in the memory array in 37 cycles [57].…”
Section: In-memory Eight-bit Adders Using Different Logic Primitivesmentioning
confidence: 99%
“…[10][11][12][13] Recent studies have identified various useful and efficient stateful gates for better computing efficiency, and as a result, stateful logic technology has advanced significantly. [14][15][16][17][18][19][20][21][22][23][24] Such various gates are possible by simultaneously applying designed operating voltages on the multiple cells. In general, the word lines of input cells and output cells are biased to a conditioning voltage (V COND ) and programming voltages (V PGM ), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the bottom panel in Figure a is more realistic. The θ is distributed and the output is a problematic function of the degree of θ variation . Then, for guaranteed gate operation, v i should be higher than the maximum amplitude of θ variation.…”
mentioning
confidence: 99%
“…In this case, the effective array size can be ( n × m ), where m is the number of selected gate lines. This configuration is useful for executing some logic gates in parallel …”
mentioning
confidence: 99%